Avaliação da perda de inserção óssea e radicular dos dentes anteriores no tratamento descompensatório das más oclusões do padrão III - Guedes, Fabio Pinto (2013)
The aim of this study is to evaluate the effects of orthodontic decompensation in buccal and lingual alveolar bone and root length - by using Cone-Beam Computed Tomography - and to analyze, from a cost-benefit perspective, the decompensation protocol adopted in patients with dentoskeletal discrepancies. Six surgically treated Class III patients, who had pre and post decompensation Cone-Beam CT were selected. On the multiplanar reconstruction screen, the sections (axial, coronal and sagittal) were made in the long axis of each incisor. From the sagittal sections, the pre and post decompensation levels of buccal and lingual bone insertion and the root lenght were calculated. The data collected was subjected to descriptive statistical analysis to calculate the amount of buccal and lingual bone insertion loss and the root length after the decompensation. Moreover, the percentage of insertion loss, considering the root length, was calculated. The results showed a significant negative impact on the bone insertion levels, especially on the lingual cortical of the mandibular incisors. The levels of bone insertion of maxillary and mandibular incisors in this study, pre and post decompensation, allow for reflection on the decompensatory treatment protocol in subjects with dentoskeletal discrepancies.